La résolution d’équations algébriques Linéaires d’ordre trois et quatre - Salma Merad (My University, 2025)
This thesis examines historical techniques for solving polynomiale quations of degrees three and four. It highlights the ingenious Tartaglia-Cardan’s method for Cubic equations, which relies on a transformation and the use of auxiliary variables, Introducing complex numbers in the irreducible case. For quartic equations, Ludovicco-Ferrari’s method reduces them to a diffe-rence of squares, requiring the resolution of an intermediate cubic equation before obtaining two quadratic equations. The study emphasizes the inventiveness of these methods, their historical con-text, And their fundamental impact on the development of algebra. ----------------------------------------------------------------------- الأطروحة تبحث في التقنيات التاريخية لحل المعادلات الجبرية الخطية من الدرجتين الثالثة والرابعة. وتسلط الضوء على طريقة TARTAGLIA-CARDAN العبقرية لحل المعادلات التكعيبية، والتي تعتمد على تحويل واستعمال متغيرات مساعدة، مما يؤدي إلى إدخال الأعداد المركبة في الحالة غير القابلة للاختزال. أما بالنسبة للمعادلات من الدرجة الرابعة ، فتعمل طريقة Ludovicco-Ferrari على تحويلها إلى فرق بين مربعين، مما يتطلب حل معادلة تكعيبية وسيطة قبل التوصل إلى معادلتين من الدرجة الثانية. ----------------------------------------------------------------------- Ce mémoire examine les techniques historiques de résolution des équations linéaires de degrés trois et quatre aux coeffcients complexes Il met en avant la méthode ingénieusede Tartaglia-Cardan pour les équations cubiques, qui re-pose sur une transformation et l’utilisation de variables axliaires, introduisat ainsi les nombres complexes dans le cas irréductible. Pour les équations quartiques, la méthode de Ludovicco-Ferrari les ramène à une différence de carrés, nécessitant la résoltion d’une équation cubique in-termédiaire Avant d’obtenir deux équations quadratiques. L’étude souligne l’inventivité de ces méthodes, leur contexte historique et leur impact fondamental sur le développement de l’algèbre.
Keywords: Third-degree equation; solution; discriminant; Coefficient; Biquadratic form.; معادلة من الدرجة الثالثة; المميز; حل; معامل; شكل ثنائي التربيع; Equation du troisime degré; racine; coeffcient; formebi-carré.